2022
DOI: 10.3389/fevo.2022.924151
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics on Social Interactions in Termites: Effects of Soldier Presence

Abstract: The organization of social insect colonies requires sophisticated mechanisms to regulate caste composition according to colony demands. In termites, the soldier caste is responsible for the inhibition of soldier differentiation, but the mechanism underlying the regulation of soldier differentiation is still unclear. In this study, we performed transcriptome analyses to identify genes expressed in workers that fluctuated in the presence of soldiers in the subterranean termite Reticulitermes speratus. First, sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…were differentially expressed in workers without soldiers compared to those with soldiers (using whole bodies without guts; Matsunami et al, 2022). However, we were unable to detect both of these genes in this study.…”
Section: Gene Expression In Soldier and Worker Antennae And Other Hea...mentioning
confidence: 53%
See 1 more Smart Citation
“…were differentially expressed in workers without soldiers compared to those with soldiers (using whole bodies without guts; Matsunami et al, 2022). However, we were unable to detect both of these genes in this study.…”
Section: Gene Expression In Soldier and Worker Antennae And Other Hea...mentioning
confidence: 53%
“…Consequently, it is possible that we failed to detect the expression patterns of chemoreception genes involved in worker‐specific roles. For example, a previous study showed that two CSP genes ( RS000584 and RS010442 ) were differentially expressed in workers without soldiers compared to those with soldiers (using whole bodies without guts; Matsunami et al, 2022). However, we were unable to detect both of these genes in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it is possible that we failed to detect the expression patterns of chemoreception genes involved in worker-specific roles. For example, a previous study showed that two CSP genes ( RS000584 and RS010442 ) were significantly highly expressed in workers without soldiers compared to those with soldiers (using whole bodies without guts; Matsunami et al, 2022). However, we were unable to detect both of these genes in this study.…”
Section: Resultsmentioning
confidence: 99%